The effectiveness of weight-belts during the squat exercise - Lander, J. E.; Simonton, R. L.; Giacobbe, J. K. F. (Medicine & Science in Sports & Exercise, 1990)
Lander et al (1) examined the effects of the use of weight belts on spinal compression and muscle activity during the squat exercise. Six experienced male trainees were examined; all subjects could squat 1.5 to 2.38 times their body weight in a squat exercise. Three conditions were examined: no weight belts, a light weight belt 7 mm thick and 10 mm wide in the center, and a heavy belt 11 mm thick and 100 mm wide along the entire belt. The experimenters also examined three loading conditions: 70%, 80%, and 90% 1 RM. All performances were filmed and digitized. Vertical, anteroposterior, and mediolateral forces were measured using a Kistler force platform. Intra-abdominal pressure (IAP) was measured using a ballloon catheter inserted in each subject's rectum. EMG signals from the rectus abdominus, the external obliques, and the erector spinae were measured. Kinematic data was generated from the digitized film. The lift was divided into 6 phases; the downward phase of the squat was P1-P3, and the upward phase was P4-P6. Joint moments were calculated using data from the force platform and from position data from the digitized film. Forces acting upon the spine were also calculated.